ChemInform Abstract: Solvothermal Syntheses, Crystal Structures, and Properties of New Mercury(II)—Thioantimonates(III) and a Mixed‐Valent Thioantimonate(III, V). Issue 20 (25th April 2013) - Tang, Weiwei; Tang, Chunying; Wang, Fang; Chen, Ruihong; Zhang, Yong; Jia, Dingxian
Abstract The new compounds (V), (VII), and (IX) crystallize in the monoclinic space group P21/c with Z = 4, and (VIII) in the monoclinic space group P21/n with Z = 2 (single crystal XRD).